Exploring Representations of Women as Teachers and Students in Old English Literature, 730 - 1050 AD - Williams, Abigail (2023)
Women in Old English texts have various roles ranging from wife and mother to queen and abbess. Although they appear far less often in the surviving source material than men, women play central roles that help to shape the early medieval English kingdoms from the eighth to the eleventh century. Their literary representations reflect their involvement in different areas of society, including education and instruction. This thesis explores the vocabulary used in examples which describe women as teachers and students. Evidence from the use of specific lemmata shows that royal and monastic women appear as teachers and learners in the corpus of Old English literature in more ways than previous studies suggested. My lexical analysis explores four Old English verbs readily associated with education and instruction (lǣran, tǣcan, leornian, and bysnian). I examine examples of these words from several Old English texts, alongside accompanying Latin texts, from the eighth to the eleventh century. An investigation of the ranges of vocabulary used to depict women in different genres and contexts demonstrates that Old English writers and translators used stock representations of female students and teachers in different contexts and roles with set wording. This examination also prompts a reconsideration of the audiences of these texts. My analysis discusses the readership of the Old English texts used in my study. I consider whether they were intended for certain groups of women and what impact these representations may have had on audiences’ perceptions of women’s roles in teaching and learning.